Three-dimensional effects of twinning in magnesium alloys. (15th April 2015) - Hazeli, K.; Cuadra, J.; Streller, F.; Barr, C.M.; Taheri, M.L.; Carpick, R.W.; Kontsos, A.
Abstract : This article provides experimental evidence on the pronounced three-dimensional surface effects caused by tension twinning at early stages of plasticity of a magnesium alloy. To achieve this goal, multiscale mechanical testing was combined with strain field, texture and surface morphology quantification. The current investigation correlates crystallography-driven, grain-scale surface roughening to the spatially heterogeneous micro- and macrostrain. It was found that tension twinning causes considerable surface extrusions and intrusions across multiple grains that are directly related to severe strain inhomogeneities.